Cost-effective adsorption of cationic dyes using ZnO nanorods supported by orange peel-derived carbon - Eman J. E. Abdelrazek; Ahmed A. Gahlan; Gamal A. Gouda; Abdelaal S. A. Ahmed (Scientific Reports)
Abstract Here, porous carbon (PC) and ZnO nanorods@PC (ZnO-NR@PC) composite derived from orange peel (OP) have been synthesized via a simple carbonization process. The prepared materials have been characterized by XRD, FT-IR, TEM, and BET analysis. The adsorptive properties of the prepared PC and ZnO-NR@PC composite have been investigated toward methylene blue (MB) and crystal violet (CV) cationic dyes from their aqueous solutions. The adsorption studies concluded that the maximum adsorption efficiency was achieved after 90 min in the basic conditions (pH = 10). Langmuir, Freundlich, Dubinin–Radushkevich (D-R), and Temkin non-linear isotherm models were applied to fit the experimental data. The adsorption of MB and CV dyes by the OP is fitted with the Freundlich model, and the adsorption of both dyes by the PC and the ZnO-NR@PC composite fitted with the Langmuir model. The estimated maximum adsorption capacity estimated from the adsorption of MB and CV by the ZnO-NR@PC composite was 74.45 and 74.89 mg/g, respectively. The calculated adsorption free energy from D-R and Temkin models indicates the adsorption of MB, and CV dye molecules by the OP, PC, and ZnO-NR@PC composite may be physical. The kinetic studies revealed the adsorption of MB and CV dyes onto the OP, PC and ZnO-NR@PC composite fitted with the pseudo-second-order model. On the otherhand, the thermodynamic studies confirmed the adsorption of MB, and CV dyes onto ZnO-NR@PC composite is an endothermic and spontaneous process. Furthermore, the prepared materials displayed high adsorption stability with an overall removal efficiency of about 90% after five cycles. The mechanism of MB and CV dyes by the ZnO-NR@PC composite is proposed to be controlled by electrostatic bonding, π-π interactions, and ion exchange. The results indicated the potential ability of OP-derived porous carbons as adsorbents for cationic dyes from aqueous media.